Innovation in public management: the adoption of strategic planning - Berry Frances Stokes
Under what conditions do state agencies innovate by adopting strategic planning? Frances Berry develops four explanations about factors that lead a state agency to adopt strategic planning: its resources, its leadership cycle, its orientation to businesss and citizens; and diffusion of strategic planning across states. Her research finds that agencies are most likely to adopt strategic planning: (1) early in gubernatorial administrations (2) under conditions of strong fiscal health (3) when agencies work closely with private sector businesses, and (4) as the number of neighboring state agencies that have already adopted strategic planning increases. Implications for practitioners are drawn on the study's findin
Keywords: Strategic Management -- U.S.A.; Stratesic Planning -- U.S.A.; Public Administration -- U.S.A.